Project State 347: Adaptability of breeds of rams and breed types of range ewes to market lamb production in Kansas - Bell, T.D.; Holland, L.A. (Kansas Agricultural Experiment Station, 2012)
During the fall of 1951, ewe lambs representing the three types of ewes commonly used in Kansas were secured from southern Utah. One-third of these 140 lambs were of straight Rambouillet or finewool breeding and similar to Texas ewes; one-third of the lambs wore sired by Columbia rams out of Columbia x Rambouillet ewes and were similar to the Northwestern whiteface croRsbred ewos commonly obtained from the Northwestern range area; and one-third of the lambs were sired by Suffolk rams and out of whiteface crossbred ewes and were similar to Northwestern blackface ewes. These ewes will be maintained at the College as long as their productive life will permit and careful records will be kept of their wool production as well as their lamb production when mated to different breeds of rams. Other factors of economic importance, such as longevity and the ability to produce early lambs, will be studied.
Keywords: Sheep; Rams; Market lamb; Fleece